PENERAPAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) UNTUK MENINGKATKAN MINAT BELAJAR SISWA KELAS X DI SMA NEGERI 10 MATARAM - Hikmah, Baiq Fitri Raudatul; Khairuddin, Khairuddin; Jumadil, Jumadil (JURNAL ASIMILASI PENDIDIKAN, 2023)
This study aims to find out the increase in interest in the application of the Teams Games Tournament (TGT) learning model in Biology subject to students X A Semester 2 at SMA Negeri 10 Mataram. The type of research used in this study was Classroom Action Research (PTK) with research subjects in class X A semester 2 at SMA Negeri 10 Mataram as many as 32 students. Meanwhile, the object of this study is students' interest in learning biology after the implementation of the Teams Games Tournament (TGT) learning model. Based on the results of the study it was found that during the pre-cycle implementation, the percentage of students who achieved a high learning interest was 46.88% of the total students, then in cycle I it increased by 9.37% to 56.25% and from cycle I to cycle II it increased by 18 .75% to 75%. Based on these data it can be concluded that the application of the TGT learning model can increase students' interest in learning biology.